Tua Ji Peh: The Intricacies of Liminality in the Deification of Chinese non-Buddhist Supernatural Beings in Chinese-Malaysian Communities - Whitney Webb (The ASIANetwork Exchange: A Journal for Asian Studies in the Liberal Arts, 2012)
The pragmatic, responsive, and syncretic nature of popular Chinese religion is well known and is thought to result, in part, from the religion’s close connection to the fluxes of the social system in which its adherents live. These characteristics often result in considerable change when the social fabric is greatly disrupted, such as in the immigration of Chinese to new and unfamiliar places. This process of change is commonly seen among Chinese deities. Tua Peh大伯 and Ji Peh 二伯 (in Hokkien dialect “First Uncle” and “Second Uncle”), two ghostly deities of popular Chinese Malaysian religion, are understood to have an ambiguous status in the Chinese pantheon as they possess characteristics of both gods and ghosts. In China, these figures were simply part of the otherworldly bureaucracy of the hell realm with a very limited role and were worshipped infrequently. In the past 20 years, their worship has become extremely ubiquitous, with many shrines and temples proliferating. Now a variety of people come to them for wealth, for healings, and for protection. This coincides during a time in which the economic situation of Chinese Malaysians has become more difficult which parallels a significant rise in political tensions between Malays and non-Malays. This has caused a shift towards favorability in the deities’ reputation, the demographics of their worshippers, and the reasons patrons seek their assistance. Overall, the elevation of Tua Ji Peh seems to work towards lending legitimacy to those desperately seeking efficacious aid in a increasingly discriminatory and poltically unstable environment with harsher realities.